Exploring Recent Life Experiences Among High School Students: Gender and Grade-Level Influences on Psychological and Behavioral Challenges - Moch. Syihabudin Nuha; Nusril Muchtadi (Pedagogy Review, 2024)
Abstract: This study will present the results of testing the current experience instrument of senior high school students who are not contaminated with certain problems. This instrument is a development of the current experience instrument in college students who are not contaminated with certain problems. The instrument consists of 41 statements divided into 8 factors namely social isolation, excessive demands, romantic problems, decisions about the future, loneliness and unpopularity, various disorders and anxiety, social persecution, and academic challenges. This instrument was adopted by the researcher with the aim of being in line with the development of this instrument, namely measuring the extent of physical and mental health disorders to be predicted. This instrument will see how influential gender is on current experiences. Testing was conducted on 48 MA Al-Khoiriyah Gondanglegi students in classes X and XII. The results of the classical assumption test have met the classical assumptions, then proceed to the independent sample T-Test test with the results of the df value of 46 so that the t-table is 2.013 (t-count 2.706) so it can be concluded that gender determines different recent experiences or in other words gender will produce different physical or mental disorders. The test continued with the chi-square test which looked at the relationship between gender and grade level on students' current experiences with a sig value of 0.000 (p 0.05) so that H1 was accepted or there was a relationship between gender and grade level on students' current experiences or in other words that gender and grade level were related to students' current experiences. It can be concluded that gender and grade level significantly influence and relate to students' current experience.   Keywords: recent life experience, maladaptive behavior, rencent behavior, psychological disorders.